Impact of performance appraisal systems used in utility companies on employee job satisfaction: The case of performance development programme used by TANESCO, Ilala region, Dar es Salaam, Tanzania, - Mwinuka,Elizabeth (Mzumbe University, 2024)
A dissertation submitted to Mzumbe University Dar es salaam Campus College in partial fulfilment of the requirements for award of the degree of Master of Business Administration (MBA) of Mzumbe University